New Attorney Swearing In Ceremony Held in State Building Auditorium - Watkins, Howard::::::::: (1987)
Side view of Assistant Clerk of the Court Vickie Hernandez administering oath to new attorneys Closest two: Patricia Mattson-Markell and James Sanchez